Spatial analysis of metformin use compared with nicotine and caffeine consumption through wastewater-based epidemiology in China - Shao, Xue-Ting; Cong, Zi-Xiang; Liu, Si-Yu; Wang, Zhuang; Zheng, Xiao-Yu; Wang, De-Gao (Ecotoxicology and environmental safety, 2021)
Monitoring the consumption of pharmaceuticals and licit drugs is important for assessing the needs of public health owing to the impact on individuals as well as society. The present work applied wastewater-based epidemiology to profile the spatial patterns of metformin, nicotine, and caffeine use and their correlations. Influent wastewater samples were collected from 27 wastewater treatment plants in 22 typical Chinese cities that covered all geographic regions of the country. The consumption of metformin ranged from 0.02 g/d/1000 inh to 8.92 g/d/1000 inh, whereas caffeine and nicotine consumption ranged from 4.33 g/d/1000 inh to 394 g/d/1000 inh and 0.17 g/d/1000 inh to 1.88 g/d/1000 inh, respectively. There were significant regional differences in the consumption of caffeine, with the highest consumption in East China and the lowest consumption in Northeast China. The consumption and concentration of caffeine were related to the gross domestic product and per capita disposable income of urban residents, respectively. There was a correlation between the concentrations of caffeine and cotinine (a nicotine metabolite), thereby indicating that individuals that use one of these substances are likely to use the other substance. A significant relationship was found between the concentration of metformin and cotinine, thereby implying that the use of tobacco may be correlated with type 2 diabetes. Co-analysis of these substances in wastewater may provide a more accurate picture of substance use situations within different communities and provide more information on human health, human behavior, and the economy. This report describes the newest study related to the consumption of metformin among the general population in China. •Nicotine is widely used and shows no clearly spatial pattern in China.•Gross domestic product affects the spatial difference in caffeine use.•Nicotine use correlates with therapeutic drug metformin for diabetes mellitus.